2004
DOI: 10.1002/ajim.20016
|View full text |Cite
|
Sign up to set email alerts
|

A disease and non‐battle injury model based on Persian Gulf War admission rates

Abstract: The level of combat must be considered. The traditional use of average or overall rates should be abandoned when forecasting DNBI rates. Medical support projections should use separate 95th percentile DNBI admission rates for each of the phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…As with prior studies demonstrating an increase in both battle-and non-battle-related injuries and illnesses during the period of combat, 24,25 diarrhea and respiratory infections were observed to be more common during the combat phase of operations in Iraq. Although unproven, the combination of an increased pace of operations along with a breakdown in the ability to provide clean water and food, appropriate hygiene, and medical resources likely led to the increase in illness.…”
Section: Discussionsupporting
confidence: 78%
“…As with prior studies demonstrating an increase in both battle-and non-battle-related injuries and illnesses during the period of combat, 24,25 diarrhea and respiratory infections were observed to be more common during the combat phase of operations in Iraq. Although unproven, the combination of an increased pace of operations along with a breakdown in the ability to provide clean water and food, appropriate hygiene, and medical resources likely led to the increase in illness.…”
Section: Discussionsupporting
confidence: 78%
“…We only studied a single BCT, so it is possible that this unit was not representative of all units in the U.S. Army. Specifically, as previous research has shown that DNBI rates vary with the intensity of combat [5], units with more or less combat exposure than the unit in our study may have different rates of psychiatric DNBI, suggesting that replication of this study in other units would be informative. Additionally, female soldiers accounted for only 7.9% of the total population at risk yet accounted for 14.6% of the total number of soldiers with a psychiatric diagnosis.…”
Section: Discussionmentioning
confidence: 74%
“…This has been delineated in great detail in studies of the American Civil War, World War I, World War II, Korean War, Vietnam War and the Persian Gulf War [1][2][3][4][5]. Many recent studies have analyzed the medical aspects of the current Operation Iraqi Freedom and Operation Enduring Freedom Conflicts [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that non-combat injuries may account for 31–36% of medical evacuations [16,28,36]. A cause-type structure of non-combat injuries was similar to that found in the literature; these were acoustic injuries caused by sports activities, specialized training, falls, and traffic accidents [16].…”
Section: Discussionmentioning
confidence: 81%